Formalisasi Aktivitas Pedagang Kaki Lima di Simpanglima Semarang - Surya, Octora Lintang (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Semarang City is one of the cities that are currently paying more attention to the informal sector especially street vendors (PKL-Pedagang Kaki Lima). The government attentions has been formulated as policy in form of street vendor’s arrangement program, which one of it is in Simpang Lima. In this setting, there are indications of attempts to formalize the activities of street vendors. There phenomena can be pursed into a research question which is the indications to formalize the activities of street vendors? The objectives of this research are to identify existing conditions of PKL activity, identifying vendors and visitor profiles, identifying the characteristics acivities of street vendors and visitors perception of the existence of street vendors and formulating indications to formalize the activities of street vendors.The used method in this study is a quantitative approach supported by quantitative descriptive analysis tools, as well as the frequency distribution method and crosstab method. According to the profile of street vendors, it is indicates that street vendors bussiness can be one of the major alternative livelihoods. In the analysis of the PKL activities characteristics, it is founded that there is a shifting characteristics of street vendors. While for the visitor profile analysis, it is found that PKL visitors come from all kinds of jobs, income level and educational background. Final formulation suggests that indicated a formalization of street vendors who have shifted the paradigm of the characteristics of a classic street vendor activity.